Optimalisasi Media Pembelajaran Digital Berbasis Multimedia dan Video Interaktif dalam Pembelajaran Pendidikan Agama Islam - Erli Yana; Luthfia Hanifatus Saiyidah; Agus Jatmiko; Meriyati Meriyati; Chairul Amriyah; Mu’adz Haidar Zulkarnain; Muhammad Rifkhi Maulana (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the optimization of digital learning media based on multimedia and interactive videos in Islamic Religious Education to enhance learning effectiveness, motivation, participation, and student comprehension. The research employs a library research method, with data collected through documentation of scientific literature, journals, books, and articles related to digital media, multimedia, and interactive videos. Data analysis was conducted using content analysis to identify, categorize, and interpret key concepts relevant to the study. Findings show that multimedia enables interactive, contextual, and engaging material presentation, while interactive videos add a participatory dimension through navigation, quizzes, and simulations. Optimization strategies emphasize integrating technology with interactive teaching methods, strengthening teacher competencies, developing adaptive curricula, and providing supporting facilities. The study concludes that digital media based on multimedia and interactive videos is effective in enhancing students’ understanding of religious concepts, internalizing Islamic values, and developing 21st-century competencies, although further empirical research is recommended.